DEPATOLOGIZATION OF TRANS IDENTITY - Mršević, Zorica (Glasnik Advokatske komore Vojvodine, 2020)
The subject of this paper are the current world trends in the depatologization of trans identities, which is one of the essential ways of protecting the human rights of persons of this identity status. Namely, the stigma and discrimination of trans and gender different people is a real and big problem all over the world, being a part of structural model of permanent oppression that takes away their essential human rights, based on the concept of illness. One of the necessary steps taken in some countries in Europe and the world is the issuance of personal identity documents without surgery or diagnosis. Also, the classification of the trans health care model from the psychiatric assessment model is transformed into an approach based on information, counseling and informed decision making. Keywords: trans and gender different persons, transphobic violence, health care modifications, personal documents, new International Classification of Diseases - ICD 11